Total Hip Arthroplasty in Mucopolysaccharidosis Type IH. (23rd January 2012) - O'hEireamhoin, S.; Bayer, T.; Mulhall, K. J.
Abstract : Children affected by mucopolysaccharidosis (MPS) type IH (Hurler Syndrome), an autosomal recessive metabolic disorder, are known to experience a range of musculoskeletal manifestations including spinal abnormalities, hand abnormalities, generalised joint stiffness, genu valgum, and hip dysplasia and avascular necrosis. Enzyme therapy, in the form of bone marrow transplantation, significantly increases life expectancy but does not prevent the development of the associated musculoskeletal disorders. We present the case of a 23-year-old woman with a diagnosis of Hurler syndrome with a satisfactory result following uncemented total hip arthroplasty.